Bardet-Biedl Syndrome, Crohn Disease, Primary Sclerosing Cholangitis, and Autoantibody Positive Thyroiditis: A Case Report and A Review of a Cohort of BBS Patients. (15th August 2012) - Halac, Ugur; Herzog, Denise
Abstract : Bardet-Biedel syndrome (BBS) is a rare autosomal recessive, genetically heterogeneous ciliopathy. Although the disease has been described in a patient with psoriasis, individuals with BBS are not known to be at risk of developing autoimmune disorders. Our objective was to describe a 14-year-old patient with BBS who presented with Crohn disease (CD), primary sclerosing cholangitis (PSC), and thyroiditis in the context of a cohort review at Sainte-Justine Hospital and to alert clinicians to the increased risk of autoimmune disorders in these patients. The cohort contained fifteen patients (9 boys), followed from 1968 to 2009 during a median period of 12 years (range 9 months–26 years). Three of the 15 patients (20%) developed a chronic autoimmune disease: one had juvenile rheumatoid arthritis; a second one had type 1 diabetes mellitus in association with Hashimoto thyroiditis and psoriasis; a third one developed CD, PSC, and Hashimoto thyroiditis. As chronic autoimmune diseases occurred in 20% of our cohort of children with BBS, it is appropriate to keep this association in mind during the followup.